MEMAHAMI REALISME MAGIS DANARTO DAN MARQUEZ - Suci Sundusiah (Center of Language and Cultural Studies, 2015)
Begun as a theme of painting art, magical realism exists as a typical place in litarature. The works of magical realism literature efforts to appear magical aspects such as superstition, beliefs, folklor and spiritual substance exceding from the logic into reality of daily lifes. The substance of the magic is integrated in the accepted traditions and cultures. This article analyzes short stories of Danarto and a novel of Marquez. Both aouthors are selected as they represent pionneers of writing style of magical realism from two different cultures. Both authors express the same writing style, but their patterns of rhetoric differ. Danarto focuses on the magical realism of religion, sufism and Javanese cultures, combining magical realism with surealism styles. In addition, Marquez brings readers to the structure of Latin American society that produces unpredictable magical cultures.